1985
DOI: 10.1177/0013916585176004
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Dispositions among School-Age Children

Abstract: The Children's Environmental Response Inventory (CERI) is introduced as a means of measuring environmental disposition, or what has been termed "environmental personality." This test is shown to have sound psychometric properties. It has been administered to a large sample of school-age children in the age range 9 to 16 years. Differences are found among responses to the eight domains: Pastoralism, Urbanism, Environmental Adaptation, Stimulus Seeking, Environmental Trust, Antiquarianism, Need Privacy, and Mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
32
0
2

Year Published

1987
1987
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 48 publications
7
32
0
2
Order By: Relevance
“…Specii cally, we proposed of nature have been shown to predict proenvironmental beliefs (Ewert, Place, Sibthorpe, 2005;Lohr & Pearson-Mims, 2005), and people with a rural childhood have been found to have more positive orientations toward the natural environment than those with an urban childhood (Bunting & Cousins, 1985;Hinds & Sparks, 2008). It has also been suggested that it is the emotional attachments that people form through experiential encounters with nature that are instrumental in developing commitments to nature (Milton, 2002).…”
Section: The Present Studymentioning
confidence: 98%
“…Specii cally, we proposed of nature have been shown to predict proenvironmental beliefs (Ewert, Place, Sibthorpe, 2005;Lohr & Pearson-Mims, 2005), and people with a rural childhood have been found to have more positive orientations toward the natural environment than those with an urban childhood (Bunting & Cousins, 1985;Hinds & Sparks, 2008). It has also been suggested that it is the emotional attachments that people form through experiential encounters with nature that are instrumental in developing commitments to nature (Milton, 2002).…”
Section: The Present Studymentioning
confidence: 98%
“…attitudes and motivations. In most cases the observation and analysis of environmental attitudes has been undertaken employing questionnaires (Whyte, 1977;McKechnie, 1974;Bunting and Semple, 1979), and of these the environmental response inventory (ERI) (McKechnie, 1977;1978) and the children's environmental response inventory (CERI) (Bunting and Semple, 1979;Bunting and Cousins, 1985) stand out. These, and similar questionnaires, are extensively applied.…”
Section: Introductionmentioning
confidence: 99%
“…8,13,15,[36][37][38][39][40][41][42]. The development of an environmental ethic may not require visits to what the child perceives as 'natural spaces' since experience, even within natural spaces of a schoolyard, help in the development of environmental concern [38,43,44]. Children may also be exposed to natural spaces in association with sporting activities, playing in the local reserve or taking a shortcut through nearby bushland.…”
Section: Discussionmentioning
confidence: 99%